CUKA APEL MENURUNKAN BERAT BADAN TIKUS DENGAN OBESITAS - Fitriyani, Fitriyani; Kurniasari, Kurniasari (Jurnal Biomedika dan Kesehatan, 2022)
BACKGROUNDObesity has become a global problem in the last ten years. The increasing incidence of obesity caused an increase number in deaths from various obesity-related diseases. Pharmacotherapy for obesity that exists today is limited and has a variety of side effects. Apple cider vinegar is one type of natural ingredient used by the general public to lose weight. Acetic acid is an active component of apple cider vinegar that plays important role in weight loss. METHODSThis study is an experimental study using experimental animals. Thirtysix Sprague Dawley rats aged 1-2 months were given high-fat diet for 5 weeks. Rats with obesity were divided into 3 groups, the control group, the P1 group were given apple cider vinegar doses of 0.096mL/100g twice daily and the P2 group were given apple cider vinegar doses of 0.192mL/100g twice daily. Treatment is given for 4 weeks. Weight and leftovers food are weighed during treatment period. The final weight was analyzed with the Kruskal-Wallis test and the weight difference was analyzed with the one-way ANOVA test followed by the Turkey post hoc test. RESULTSThere was no difference in final weight between the 3 groups (p=0.55), but there was a significant difference in weight before and after treatment between the control group and the P1 group (p=0.001) and the control group with the P2 group (p=0.000). CONCLUSIONApple vinegar has the potential to be used as an anti-obesity treatment in obese subjects. KEYWORDS : Obesity, Apple Cider Vinegar, Weight Loss